61OSafety, anti-tumour activity, and biomarker results of the HER2-targeted bispecific antibody ZW25 in HER2-expressing solid tumours. (24th November 2019) - Oh, D-Y; Hamilton, E; Hanna, D; Beeram, M; Lee, K-W; Kang, Y-K; Chaves, J; Lee, J-Y; Goodwin, R; Vaklavas, C; Rha, S-Y; Elimova, E; et al.
Abstract: Background: ZW25, a novel IgG1 bispecific antibody, targets HER2 domains ECD2 and ECD4, resulting in multiple differentiated and unique mechanisms of action, including improved receptor internalization and downregulation relative to trastuzumab. Safety, anti-tumor activity, and biomarker data from an ongoing phase 1 trial of ZW25 monotherapy in solid tumors other than breast cancer, are presented here. Methods: Eligible patients with HER2 IHC 3+, IHC 2+/FISH+, or IHC 2+/FISH- tumors confirmed by central review of fresh or archival biopsies, who had progressed on all standard therapies, were enrolled. Patients were treated with single agent ZW25 at 10 mg/kg QW or 20 mg/kg Q2W Assessments included tumor evaluations (RECIST 1.1 Q8W), circulating tumor DNA (ctDNA), and standard safety evaluations. Results: A total of 43 patients were treated, including 17 patients with gastroesophageal adenocarcinoma (GEA), 6 with biliary cancers, 10 with colorectal cancer, and 10 other cancers. The median number of prior therapies was 3 (range 1-6) for all patients. For GEA and non-GEA patients, 88% and 35% respectively received at least one prior HER2 therapy. The most common treatment-related adverse events (all Grade 1 or 2) were diarrhea (49%) and infusion related reaction (34%). The objective response rate (all partial response (PR)) for response evaluable patients was 41% (14/34), stable disease (SD) in 38% (13/34), and progressive disease in 21% (7/34). The majority of patients (74%; 25/34) experienced a decrease in the sum of diameters for their target lesions. Compared to FISH, the positive predictive value of HER2 amplification in pre-dose C1D1 ctDNA was 90% (95% CI 79-96%), negative predictive value 45% (25-67%), and diagnostic accuracy 79% (63-90%). Disease control (PR or SD) > 5 months was associated with lower level of copy number adjusted mutational variant allele frequency in pre-treatment ctDNA (Mann Whitney p = 0.0085). Conclusions: ZW25 has been well tolerated with promising single agent activity in heavily pre-treated patients. These data support further clinical development of this bispecific antibody in HER2-expressing solid tumors. Clinical trial identification: Identifier: NCT02892123. Legal entity responsible for the study: Zymeworks Inc. Funding: Zymeworks Inc. Disclosure: D-Y. Oh: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Novartis; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Bayer; Advisory / Consultancy: Taiho; Advisory / Consultancy: ASLAN; Advisory / Consultancy: Halozyme; Advisory / Consultancy: Zymeworks; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Novartis; Research grant / Funding (self): Array; Research grant / Funding (self): Eli Lilly; Research grant / Funding (self): Green Cross. E. Hamilton: Speaker Bureau / Expert testimony: Genentech/Roche; Advisory / Consultancy: Flatiron Health; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Casadian Therapeutics; Research grant / Funding (self): Zymewors; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Casadian Therapeutics; Research grant / Funding (self): Hutchinson. M. Beeram: Speaker Bureau / Expert testimony: Genentech. K-W. Lee: Honoraria (self): BMS; Honoraria (self): Eli Lilly; Research grant / Funding (self): ALX Oncology; Research grant / Funding (self): Array BioPharma; Research grant / Funding (self): ASLAN Pharma; Research grant / Funding (self): AstraZeneca/MedImmune; Research grant / Funding (self): Five Prime; Research grant / Funding (self): Green Cross Corp; Research grant / Funding (self): LSK BioPharma; Research grant / Funding (institution): Macrogenics; Research grant / Funding (self): Merck MGaA; Research grant / Funding (self): MSD; Research grant / Funding (self): Ono Pharma; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Pharmacyclics; Travel / Accommodation / Expenses: BMS. Y-K. Kang: Advisory / Consultancy: ONO; Advisory / Consultancy: BMS; Advisory / Consultancy: Daehwa; Advisory / Consultancy: LSK BioPharma; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Macrogenics; Advisory / Consultancy: Zymeworks; Advisory / Consultancy: Blue print; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Novartis; Advisory / Consultancy: Astellas; Research grant / Funding (self): Roche; Research grant / Funding (self): Novartis. J. Chaves: Honoraria (self): PLLC. C. Vaklavas: Advisory / Consultancy: Genentech; Advisory / Consultancy: Daiichi-Sankyo; Research grant / Funding (self): Genentech; Research grant / Funding (self): Roche; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Incyte; Research grant / Funding (self): Novartis; Research grant / Funding (self): Pharmacyclics; Research grant / Funding (self): Tracon; Research grant / Funding (self): Innocrin; Research grant / Funding (self): Zymeworks; Research grant / Funding (self): H3 Biomedicine. E. Elimova: Advisory / Consultancy: BMS; Honoraria (self): Zymeworks; Spouse / Financial dependant, Spouse: Merck employee in vaccine global division: Merck. C. Ferrario: Honoraria (self): Pfizer; Honoraria (self): Bayer; Honoraria (self): Novartis; Honoraria (self): AstraZeneca; Honoraria (self): Merck; Honoraria (self): Astellas; Advisory / Consultancy: Genomic health; Advisory / Consultancy: Merck; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Bayer; Speaker Bureau / Expert testimony: Novartis; Research grant / Funding (self): Amgen; Research grant / Funding (self): Astellas; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Bayer; Research grant / Funding (self): Casadian Therapeutics; Research grant / Funding (self): Celldex; Research grant / Funding (self): Lilly; Research grant / Funding (self): Merck; Research grant / Funding (self): Novartis. A. Fortenberry: Shareholder / Stockholder / Stock options, Full / Part-time employment: Zymeworks. G. Rowse: Shareholder / Stockholder / Stock options, Full / Part-time employment: Zymeworks. T. Gray: Shareholder / Stockholder / Stock options, Full / Part-time employment: Zymeworks. R. Lai: Shareholder / Stockholder / Stock options, Full / Part-time employment: Zymeworks. F. Meric Bernstam: Research grant / Funding (self): Novartis; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Calithera; Research grant / Funding (self): Aileron; Research grant / Funding (self): Bayer; Research grant / Funding (self): Jounce; Research grant / Funding (self): CytoMx; Research grant / Funding (self): eFFECTOR; Research grant / Funding (self): Zymeworks; Research grant / Funding (self): PUMA Biotech; Research grant / Funding (self): Curis; Research grant / Funding (self): Millennium; Research grant / Funding (self): Daiichi Sankyo; Research grant / Funding (self): AbbVie; Research grant / Funding (self): Guardant Health; Research grant / Funding (self): Takeda, Seattle Genetics, GlaxoSmithKline; Research grant / Funding (self), Travel / Accommodation / Expenses: Taiho, Genentech, Debiopharm Group, Pfizer; Consulting: Pieris, Dialectica, Sumitomo Dainippon, Samsung Bioepis, Aduro, OrigiMed, Xencor, Jackson Laboratory, Zymeworks, Kolon Life Science, Parexel Internationa; Advisory / Consultancy: Inflection Biosciences, GRAIL, Darwin Health, Spectrum, Mersana, and Seattle Genetics. All other authors have declared no conflicts of interest.